Willey P., Eagle’s Nest: Ismaili Castles in Iran and Syria, London-New York, I.B. Tauris, 2006, 321 p. - Gonzalez, Valérie (Revue des mondes musulmans et de la Méditerranée, 2008)
Old myths are very difficult to deconstruct, even when historical evidence reveals the absurdity of their foundations. The infamous “assassin” legend that from the Middle Ages soils the memory of the Nizari Ismaili community is an example of this incorrigible defect of the collective consciousnesses. The image presented by both Christian and Muslim chroniclers of the Ismailis as unscrupulous terrorists is unfortunate if their sole fault lay in surviving as a distinct political and religious c...